1999
DOI: 10.1177/0887302x9901700302
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between South Korean Male and Female Consumers in the Clothing Brand Loyalty Formation Process: Model Testing

Abstract: Although considerable research on brand loyalty has been conducted, few attempts have been made to integrate the results of previous studies. This study focuses on causal relationships among brand loyalty-related variables, such as consumer knowledge, product involvement, perceived risk, information search, and consumer satisfaction, in an effort to integrate results of previous studies. The purpose of this study was to propose a model of clothing brand loyalty formation considering the five brand loyalty-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 40 publications
1
26
1
Order By: Relevance
“…Korea is a culture of strong uncertainty avoidance and collectivism, and its consumers exhibit a high level of brand loyalty and quality consciousness (Jin and Koh, 1999). While this study found differing effects of consumer variables on PB attitude and intention by product categories, it may not an issue of the product categories investigated, but rather the combined effect of cultural dimensions on consumption.…”
Section: Limitations and Future Studiesmentioning
confidence: 56%
“…Korea is a culture of strong uncertainty avoidance and collectivism, and its consumers exhibit a high level of brand loyalty and quality consciousness (Jin and Koh, 1999). While this study found differing effects of consumer variables on PB attitude and intention by product categories, it may not an issue of the product categories investigated, but rather the combined effect of cultural dimensions on consumption.…”
Section: Limitations and Future Studiesmentioning
confidence: 56%
“…Numerous studies have confirmed that perceived risk affects consumers' attitudes (Featherman & Pavlou, 2003;Lee, Kim, & Fiore, 2010;Park & Kim, 2007;Verhagen, Meents, & Tan, 2006) and purchase intentions (Choi & Lee, 2003;Gaal & Burns, 2001;Han & Chung, 2014;Jin & Koh, 1999;Park, Lennon, & Stoel, 2005). For instance, two online shopping studies found that perceived risk negatively influenced attitudes toward online retailers (Lee et al 2010;Verhagen et al, 2006).…”
Section: Perceived Risk Attitudes and Purchase Intentionsmentioning
confidence: 87%
“…Dressing well or properly, especially in a public setting, is extremely important in keeping face in Confucian cultures (Jin & Koh, 1999). Face-saving was found to be still important among young Chinese consumers in forming attitude as well as in determining purchase intention.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…However, face has much greater social significance among Chinese than do similar notions among Americans (Hu & Grove, 1999). In a Confucian culture, dressing properly, especially in a public setting, is important to keep one's face (Jin & Koh, 1999), which may be an important motivation to buy expensive foreign brand apparel. Therefore, individuals are always under strong pressure to act to meet the expectations of others so as to maintain face.…”
Section: Literature Review Chinese Traditional Valuesmentioning
confidence: 99%